Botulinum toxin and hyaluronic acid — the most common facial aesthetic medicine treatments — the economic aspect in terms of price in 2019 in Poland (Journal of Face Aesthetics, 2020)
Introduction. The observed intensive quantitative growth of aesthetic medicine clinics on the market may lead to a lowering of the general price level, although nowadays the high quality of services is a factor that determines the choice of a surgery more often than a low price.Aim. Estimate of average prices of selected facial aesthetic medicine’s procedures in Poland in 2019.Material and Methods. 7 types of facial aesthetic medicine treatments with the use of botulinum toxin or fillers that were used in 112 clinics located in Poland in 2019 were taken for the analysis.Results. The highest prices for wrinkle reduction with botulinum toxin were in the Mazowieckie Voivodeship and the lowest in the Podlasie Voivodeship. Treatments with the use of fillers cost the least in Kuyavian-Pomeranian, and the most in Mazowieckie. The most expensive treatment among the examined was the correction of the shape of the lips - 910 PLN and the cheapest was the reduction of wrinkles around the eyes - 460 PLN.Discussion. Higher prices than average can be expected in provincial cities. This is often dictated by the level of service innovation and / or patient wealth. Sometimes offering lower prices than the average can be an effective way to attract customers.Results. Treatments with the use of fillers are more expensive than those with the use of botulinum toxin by almost half. Most surgeries offer services in the field of facial aesthetic medicine using botulinum toxin and / or fillers at comparable prices.
Keywords: aesthetic medicine; filler; botulinum toxin; price; market competition; medical services market